If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 = 2(5x + 3) Reorder the terms: 86 = 2(3 + 5x) 86 = (3 * 2 + 5x * 2) 86 = (6 + 10x) Solving 86 = 6 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 86 + -10x = 6 + 10x + -10x Combine like terms: 10x + -10x = 0 86 + -10x = 6 + 0 86 + -10x = 6 Add '-86' to each side of the equation. 86 + -86 + -10x = 6 + -86 Combine like terms: 86 + -86 = 0 0 + -10x = 6 + -86 -10x = 6 + -86 Combine like terms: 6 + -86 = -80 -10x = -80 Divide each side by '-10'. x = 8 Simplifying x = 8
| A+8/3=28 | | (x-10)^2/5=(9x)^1/5 | | 2(16-4x)+22=30 | | 8n-7/4=-1 | | (1/3)-(19/(4x))=(1/4)-(1/(6x)) | | 5(y-3)=-1(y+6) | | -10n+3(8+8n)=-6n(n-4) | | 4(1-5x)-5x(7x-2)= | | 125=-4(2+3x)-7x | | 250-Q^2=4Q | | 8(w+8)-(2+6w)=w | | 1/138(11x+9x)-13=19/345x | | 390/(5(7+6)) | | 1/3-19/(4x)=1/4-1/6x | | 7x+8-3=12 | | 3(2x-1)+(3/2)(3x+4)=1-4x | | 6/(x+7)=8/x | | 3x^2-8=40 | | -3+8=27 | | 0.03(x-6)+0.02(x-4)=5.24 | | 10n+3(8+8n)=6n(n-4) | | 2x+x-3=45 | | X-1=-1+3x | | 19+5-8*4/2= | | 2x^4+11x^2+15=o | | 6/x+7=8/x | | 8-7k+3=-10 | | -1(4x-5)=x | | 2(x-8)+7=5(x+2)-3x-1 | | 4f+g=-2f-14 | | (x^2-2x-8)/(x^3+x^2-2x) | | 2.5y+7.5y=4.2 |